SISTEM REKOMENDASI PEMBELIAN SMARTPHONE - Sebastian, Davin; Beng, Jap Tji; Wasino (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The development of communication technology allows people to interconnected with each other without being limited by distance, space and time. Smartphone is one of the communication tools that is now widely used by everyone as a communication tool between people. And now many companies offer a variety of smartphone products, but it provides difficulties to everyone in choosing the most suitable smartphone for them. Therefore a recommendation system is needed to overcome these difficulties. In this study a smartphone purchase recommendation system was made based on other user ratings, a smartphone brand that uses the collaborative filtering method. This system can recommend a smartphone brand based on the results of the similarity calculation of the users who later one user will be compared to another user then from the comparison results between users searched for the Similarity value that is closest to 1 which means similar.